BLACK'S WOMAN DISCRIMINATION IN NOVEL HIDDEN FIGURES BY MARGOT LEE SHETTERLY A POSTCOLONIAL APPROACH - Gultom, Sellyca Natasha; Rudianto, Gaguk (LPPM Universitas Putera Batam, 2022)
This Research is to analyze discrimination by main characters especially Black women in Hidden Figures Novels and describe the form of discrimination. And this research, researcher use discrimination theory of Parrillo Vincent. In this research design, researcher uses qualitative descriptive the source data is from Novel Hidden figures which was published in 2016, after that the reading, selecting, writing, sorting and categorization the data found. In research observed method and uses Nonparticipatory observation which researcher is not directly in research. The researcher found the data all form discrimination based on experienced by main characters which are involved Katherine, Mary jakson and Dorothy. There are from of discrimination such as verbal expression, avoidance, exclusion, physical abuse, extermination.